Meningkatkan Nilai Ekonomi UMKM melalui Ekonomi Kreatif dan Design Preneurship - Marisa Astuti; Rudy Farid; Fajar Persada Supandi (SAFE-Network, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in a country's economy, but are often faced with various challenges that limit their ability to develop. In facing the era of globalization and digital transformation, the concepts of creative economy and design preneurship have emerged as promising solutions. This research aims to analyze and understand the role of the creative economy and design preneurship in increasing the economic value of MSMEs. Data from a number of references highlights that the implementation of the creative economy and design preneurship can produce innovation, product differentiation and expand market share. Despite the great potential, many MSMEs have not fully utilized these concepts. Therefore, this research focuses on identifying effective strategies, best practices, and the impact of implementing the creative economy and design preneurship on the growth and sustainability of MSME businesses. This study uses qualitative methods with a focus on case studies. Data was obtained from 25 business actors who are MSMEs in Parongpong District, West Bandung Regency and are considered representative who will successfully apply creative economic concepts and design preneurship in increasing the economic value of MSMEs. From the research results, it is known that increasing the economic value of MSMEs through the creative economy and designpreneurship in MSMEs in Parongpong District, West Bandung Regency can be done through 3 (three) activities, namely optimizing product branding, optimizing packaging design and optimizing promotional media, with training provided regarding optimization. These three things mean that the creative economy and design entrepreneurship can effectively increase the economic value of MSMEs and provide the basis for more concrete and efficient policy strategies.